Perceived satisfaction and household fuel transition: evidence from Ugandan households - Elasu, Joseph; Ntayi, Joseph Mpeera; Adaramola, Muyiwa S.; Buyinza, Faisal; Atukunda, Ronnette; Ngoma, Muhamad (Frontiers in Sustainability, 2024)
The dominance of biomass for cooking has implications for the country. For instance, biomass conversion using traditional technologies (three stone) in poorly ventilated kitchens produce smoke that influences the reproductive health outcomes for expectant mother.Beyond health outcomes, uncontrollable harvesting of biomass for cooking contributes to environmental degradation. Unfortunately, biomass in form of firewood, charcoal, plant and animal wastes is widely consumed by more than 94% of Ugandan households for cooking. This paper examined whether perceived satisfaction plays a significant role in household energy transition in Uganda.The study adopted a panel data methodology employing an ordered logit model with random effects to estimate the effect of perceived satisfaction on household fuel transition from high to low pollutant cooking fuels in Uganda. The data used was obtained from Uganda Bureau of Statistics (UBoS) which is mandated by an Act of parliament to develop and maintain a national statistics system to ensure collection, analysis and publication of integrated, relevant, reliable and timely statistical information.Findings and discussion: Our findings demonstrate that perceived satisfaction influences household fuel transition decisions in Uganda. The study concluded by suggesting policy recommendations for government action.